Mediterranean Seafarers in Transition Maritime Labour, Communities, Shipping and the Challenge of Industrialization 1850s - 1920s - Delis, Apostolos; Ibarz, Jordi; Sydorenko, Anna; Barbano, Matteo (Brill, 2022)
This volume discusses the effects of industrialization on maritime trade, labour and communities in the Mediterranean and Black Sea from the 1850s to the 1920s. The 17 essays are based on new evidence from multiple type of primary sources on the transition from sail to steam navigation, written in a variety of languages, Italian, Spanish, French, Greek, Russian and Ottoman. Questions that arise in the book include the labour conditions, wages, career and retirement of seafarers, the socio-economic and spatial transformations of the maritime communities and the changes in the patterns of operation, ownership and management in the shipping industry with the advent of steam navigation. The book offers a comparative analysis of the above subjects across the Mediterranean, while also proposes unexplored themes in current scholarship like the history of navigation. Contributors are: Luca Lo Basso, Andrea Zappia, Leonardo Scavino, Daniel Muntane, Eduard Page Campos, Enric Garcia Domingo, Katerina Galani, Alkiviadis Kapokakis, Petros Kastrinakis, Kalliopi Vasilaki, Pavlos Fafalios, Georgios Samaritakis, Kostas Petrakis, Korina Doerr, Athina Kritsotaki, Anastasia Axaridou, and Martin Doerr.